PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN RESTO WAROENG STEAK AND SHAKE PEKANBARU - Syahsudarmi, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2016)
This study aims to determine the effect of the dimensions of service quality to customer satisfaction at Waroeng Steak and Shake restaurant Pekanbaru. Measuring the quality of service using five dimensions consisting of tangible, reliability, responsiveness, assurance, and empathy. The research instrument used was a questionnaire distributed to 30 customers were taken using purposive sampling technique. The collected data were analyzed using multiple linear regression to determine the effect of service quality to customer satisfaction and to determine the most dominant influence on customer satisfaction Waroeng Steak and Shake restaurant Pekanbaru. The results of this study showed that the five dimensions of service quality variables simultaneously and partially significant effect on customer satisfaction in the restaurant Waroeng Steak and Shake Pekanbaru. While most dominant factor affecting the reliability or customer satisfaction is followed by a variable reliability and responsiveness, assurance, empathy, and tangible